2021
DOI: 10.1021/acs.inorgchem.1c01729
|View full text |Cite
|
Sign up to set email alerts
|

Study on Phenanthroline Carboxamide for Lanthanide Separation: Influence of Amide Substituents

Abstract: Phenanthroline carboxamide compounds are promising for lanthanide intra-series separation. This paper presents a study on the effect of structure modification of phenanthroline carboxamides on the extraction of the whole lanthanide series. The study consists of theoretical calculations, extraction experiments of the 14 stable lanthanides, and extended X-ray absorption fine structure (EXAFS) analyses of Nd and Dy complexes. Tridentate monocarboxamides and tetradentate dicarboxamides show different trends in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…synthesized and studied the extractability and complexation properties of lanthanides with N -methyl- N -phenyl-1,10-phenanthroline-2-carboxamide (MePhPTA) and N -octyl- N -tolyl-1,10-phenanthroline-2-carboxamide (OcTolPTA) (Figure e). , They found that MePhPTA exhibited high extractability for Eu 3+ even under highly acidic conditions, and a slight difference in the ionic radii of Ln 3+ hardly affected the coordination properties of PTA . Furthermore, Simonnet et al, Hasegawa et al, Nakase et al, and Liu et al reported that many factors would affect the extraction behavior of those ligands, such as side chain substituents and lanthanide types, and recently, it has been discovered that the anionic system had a strong influence on the extraction performance of ligands and metals . The presence of appropriate substituents in the amide moiety, such as ethyl substituents on the amide N atom, enhances the selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…synthesized and studied the extractability and complexation properties of lanthanides with N -methyl- N -phenyl-1,10-phenanthroline-2-carboxamide (MePhPTA) and N -octyl- N -tolyl-1,10-phenanthroline-2-carboxamide (OcTolPTA) (Figure e). , They found that MePhPTA exhibited high extractability for Eu 3+ even under highly acidic conditions, and a slight difference in the ionic radii of Ln 3+ hardly affected the coordination properties of PTA . Furthermore, Simonnet et al, Hasegawa et al, Nakase et al, and Liu et al reported that many factors would affect the extraction behavior of those ligands, such as side chain substituents and lanthanide types, and recently, it has been discovered that the anionic system had a strong influence on the extraction performance of ligands and metals . The presence of appropriate substituents in the amide moiety, such as ethyl substituents on the amide N atom, enhances the selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…Since the antenna effect is extremely interesting from fundamental point of view, many theoretical and spectroscopic studies discussed the photophysical process of absorption of light, the excited state energy transfer from the ligand to the europium ion and the luminescent properties of these compounds [ 30 , 31 , 32 , 33 , 34 ]. Application-oriented investigations on phenanthroline-based complexes also demonstrated their importance for the advance technologies [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying and characterizing solution structures can be done computationally through electronic structure computations and molecular dynamics simulations , and experimentally through X-ray absorption, NMR spectroscopy, and excitation/emission spectroscopy. In particular, ab initio molecular dynamics (AIMD) simulations and extended X-ray absorption fine structure (EXAFS) spectroscopy have both been used to successfully characterize several solvated lanthanide and actinide structures. Most of the published research utilizing these techniques has centered on the structure of the ion within aqueous solutions, either as a dissolved salt or bound to chelators useful for heavy-metal extraction and biomedical applications. Despite the importance of nonaqueous solutions for several of the applications cited above, far fewer studies examine the ion coordination spheres of such ions in organic solutions beyond resolving the structures of liquid–liquid-extracted ion–ligand complexes. ,, …”
Section: Introductionmentioning
confidence: 99%